Type and Density of Zooplankton in The Pekak Lake Buluh Nipis Village, Siak Hulu Sub District, Kampar District, Riau Province - S Sinaga, Jefri Daniel; Siagian, Madju; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract The existence of human activities around the Pekak Lake producing organic  and anorganic materials that enter the water and affects the type and density of zooplankton in general. To understand the types and density of zooplankton in the Pekak Lake, a research has been carried out in March-April 2018. There were three sampling points, namely in the inlet, in the middle of the lake, and in the end of the lake. In each sampling point, the water was sampled from the surface and 0.75 m depth. Water quality parameters measured were temperature, transparency, dissolved oxygen, pH, nitrate and phosphate. Sampling were conducted 3 times, once/week. Results shown that there were 15 species of zooplankton present and they were belonged to 12 classes, namely Ciliata (3 species), Crustacea (2 species), Copepoda (1 species), Sagittoidae  (1 species), Insecta (1 species), Cladocera (1 species), Adenophorea (1 species), Suctoria (1 species), Monogononta (1 species), Sarcodina (1 species), Seisonidae (1 species), Rotifera (1 species). The zooplankton density in the Pekak Lake was 2.466-5.277 organisms/L. The most common zooplankton in Pekak Lake is Ciliate. Water quality parameter values are as follow, temperature was 27-30 0C, transparency was 68.5-76.8 cm, dissolved oxygen was 5.13-6.4 mg/L, pH  5.0, CO2 was 8.23-15,58mg/L, nitrate was 0.05-0.19 mg/L and phosphate was 0.06-0.11 mg/L. Based on the density of zooplankton, the Pekak Lake can be categorized was oligotrophic.Keywords : Kampar River, Oxbow Lake, Eutrophic, Ciliate.